Identification of defensive antimicrobial compounds from environmental Serratia marcescens SNB-CN88 strain associated with macro-holobiont (termite nest) using a molecular network approach - Nguyen, Dung; Levasseur, Marceau; Segret, Juliette; Sorres, Jonathan; Hebra, Téo; Touboul, David; Eparvier, Véronique (Comptes Rendus. Chimie, 2024)
Environmental microbes are an underexploited resource for the discovery of bioactive compounds. An integrated approach combining reversed-phase high-performance liquid chromatography and high-resolution tandem mass spectrometry with the use of molecular networks was applied to annotate novel chemical structures with potential antimicrobial activities. This metabolomic approach coupled with biological screening of environmental strains allowed the identification of 22 compounds, including 11 glucosamine derivatives and 10 cyclopeptides, from a bacterial strain of Serratia marcescens. Three new glucosamine derivatives and two stephensiolides were annotated. Two antibacterial stephensiolides, named stephensiolides E and F, were isolated to confirm annotations.